Influence of plant species, mycorrhizal inoculant, and soil phosphorus level on arbuscular mycorrhizal communities in onion and carrot roots - Ilyas, Umbrin; du Toit, Lindsey J.; Hajibabaei, Mehrdad; McDonald, Mary Ruth (Frontiers in Plant Science, 2024)
Arbuscular mycorrhizal fungi (AMF) are ancient and ecologically important symbionts that colonize plant roots. These symbionts assist in the uptake of water and nutrients, especially phosphorus, from the soil. This important role led to the development of AMF inoculants for use as bio-fertilizers in agriculture. Commercial mycorrhizal inoculants are increasingly popular in the production of onion and carrot, but their specific effects on native mycorrhizal communities in field conditions is not known. Furthermore, adequate availability of nutrients in soils, specifically phosphorus, can reduce the diversity and abundance of AMF communities in roots. The type of crop grown can also influence the composition of AMF communities colonizing plant roots. This study aimed to investigate how AMF inoculants, soil phosphorus levels, and plant species influence the diversity of AMF communities colonizing the roots of onion and carrot plants. Field trials were conducted on a high organic matter (muck) soil in the Holland Marsh, Ontario, Canada. The treatments included AMF-coated seeds (3 to 5 propagules of Rhizophagus irregularis per seed) and non-treated seeds of onion and carrot grown in soil with low (~46 ppm) and high (~78 ppm) phosphorus levels. The mycorrhizal communities colonizing onion and carrot roots were identified by Illumina sequencing. Five genera, Diversispora, Claroideoglomus, Funneliformis, Rhizophagus, and Glomus, were identified in roots of both plant species. The AMF communities colonizing carrot roots were more diverse and richer than those on onion roots. Diversispora and Funneliformis had a 1.3-fold and 2.9-fold greater abundance, respectively, in onion roots compared to carrots. Claroideoglomus had 1.4-fold greater abundance in carrot roots compared to onions. Inoculating with R. irregularis increased Rhizophagus abundance and richness in AMF communities of onion roots, but not in carrot roots. There was no effect of the soil phosphorus level on the richness and diversity of AMF in the roots of either crops. In summary, AMF inoculant and soil phosphorus levels influenced the composition AMF communities colonizing roots of onion and carrot plants, but the effects varied between the plant species.